Hadith #2197 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ahmed bin Salah al-Masri أحمد بن صالح المصري; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; ibn Abbas; Ma'mar bin Rashid معمر بن راشد; Muhammad bin 'AR bin Thauban محمد بن عبد الرحمن بن ثوبان; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان (Sunan Abi Dawud)
Mujahid said “I was with Ibn ‘Abbas”. A man came to him and said that he divorced his wife by three pronouncements. I kept silence and thought that he was going to restore het to him. He then said “A man goes and commits a foolish act and then says “O, Ibn ‘Abbas! Alaah has said “And for those who fear Allaah, He (ever) prepares a way out.” Since you did not keep duty to Allaah I do not find a way out for you. You disobeyed your Lord and your wife was separated from you. Allaah h
Grade: Sahih

Hadith #2203 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Sulaiman bin Harb سليمان بن حرب (Sunan Abi Dawud)
A’ishah said The Apostle of Allaah(ﷺ) gave us our choice and we chose him so that was not reckoned anything (i.e., divorce)
Grade: Sahih

Hadith #2215 - Sunan Abi Dawud - Aban bin Tghlb أبان بن تغلب; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
A similar tradition has been transmitted by Ibn Ishaq with a different chain of narrators. But in this version he said ‘Araq is a date-basket holding thirty sa’s. Abu Dawud said “This version is sounder than that of Yahya bin Adam.”
Grade: Hasan

Hadith #2261 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ahmed bin Salah al-Masri أحمد بن صالح المصري; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد (Sunan Abi Dawud)
The tradition mentioned above has also been narrated by Al Zuhri through a different chain of narrators to the same effect. This version adds “At that time he was hinting at disowning the child.”
Grade: Sahih

Hadith #2283 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abdullah bin Yazid al-Makhzumi عبد الله بن يزيد المخزومي المقريء; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Fatima bint Qays; Imam Maalik مالك بن أنس بن مالك بن أبي عامر (Sunan Abi Dawud)
The Prophet (ﷺ) divorced Hafsah, but he took her back in marriage.
Grade: Sahih

Hadith #2284 - Sunan Abi Dawud - Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Fatima bint Qays; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan Abi Dawud)
Abu Salamah bin ‘Abd Al Rahman reported on the authority of Fatimah daughter of Qais Abu ‘Amr bin Hafs divorced her (Fatimah daughter of Qais) absolutely when he was away from home and his agent sent her home barley. She was displeased with it. He said “I swear by Allah, you have no claim on us. She then came to Apostle of Allah (ﷺ) and mentioned that to him. He said to her “No maintenance is due to you from him. He ordered her to spend the waiting period in the house of Umm Sharik but
Grade: Sahih

Hadith #2285 - Sunan Abi Dawud - Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي; Fatima bint Qays; Mhmwd bin Khalid محمود بن خالد; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan Abi Dawud)
Abu Salamah bin ‘Abd Al Rahman said that Fatimah daughter of Qais told him that Abu Hafs Al Mughirah divorced her three times. He then narrated the rest of the tradition. The version has Khalid bin Walid and some people of Banu Makhzum came to the Prophet (ﷺ) and said Prophet of Allaah (ﷺ) Abu Hafs Al Mughirah divorced his wife three times and he has left a little for her. He said “No maintenance is necessary for her. He then transmitted the rest of the tradition. The tradition narrated
Grade: Sahih

Hadith #2286 - Sunan Abi Dawud - Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Fatima bint Qays; Isma'il bin Ja'far bin Abi Kathir إسماعيل بن جعفر بن أبي كثير الأنصاري; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
Abu Salamah reported on the authority of Fatimah daughter of Qais that Abu ‘Amr bin Hafs Al Makhzumi divorced her three times. He then narrated the rest of the tradition. He then mentioned about Khalid bin Walid and said that the Prophet (ﷺ) said “There are no maintenance and dwelling for her.” This version has “The Apostle of Allaah(ﷺ) sent a message to her “Do not give her consent for marriage without my permission.””
Grade: Sahih

Hadith #2334 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muslim bin Ibrahim al-Azdy مسلم بن إبراهيم الأزدي الفراهيدي; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan Abi Dawud)
AbuIshaq reported on the authority of Silah: We were with Ammar on the day when the appearance of the moon was doubtful. (The meat of) goat was brought to him. Some people kept aloof from (eating) it. Ammar said: He who keeps fast on this day disobeys AbulQasim (i.e. the Prophet) (ﷺ).
Grade: Sahih

Hadith #2335 - Sunan Abi Dawud - Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ahmad bin Hanbal أحمد بن حنبل; Muhammad bin Ibrahim bin al-Harith محمد بن إبراهيم بن الحارث; Muhammad bin Ja'far bin Abi Kathir محمد بن جعفر بن أبي كثير; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Tauba al-'Anbari al-Basri توبة العنبري البصري; Umm Salamah (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: Do not fast one day or two days just before Ramadan, except in the case of a man who has been in the habit of observing the particular fast, for he may fast on that day.
Grade: Sahih

Hadith #2349 - Sunan Abi Dawud - Abdul A'ala bin Hamad bin Nasr al-Bahli عبد الأعلى بن حماد بن نصر الباهلي النرسي; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة (Sunan Abi Dawud)
When the verse “Until the white thread of dawn appear to you distinct from its black thread” was revealed, I took a white rope and a black rope, and placed them beneath my pillow ; and then I looked at them, byt they were not clear to me. So I mentioned it to the Messenger of Allah (ﷺ). He laughed and said: Your pillow is so broad and lengthy ; that is (i.e. means) night and day. The version of the narrator ‘Uthman has: That is the blackness of night and whiteness of day.
Grade: Sahih

Hadith #2352 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Wahb bin Bqyh bin 'Uthman وهب بن بقية بن عثمان (Sunan Abi Dawud)
We went along with the Messenger of Allah (ﷺ) while he was fasting. When the sun set, he said to Bilal: Bilal, come down and prepare barley beverage for us. He said: Messenger of Allah, would that you waited for the evening. He said: Come down and prepare barley beverage for us. He said: Messenger of Allah, the say still remains on you (i.e. there remains the brightness of the day). He said: Come down and prepare barley drink for us. So he came down and prepared barley drink. The Messenger of
Grade: Sahih

Hadith #2392 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Hisham bin Sa'd al-Madni هشام بن سعد المدني أبو عباد; Ja'far bin Msafr bin Rashid جعفر بن مسافر بن راشد; Muhammad bin Abi Fadayk محمد بن إسماعيل بن مسلم بن أبي فديك (Sunan Abi Dawud)
(A man broke his fast intentionally) during Ramadan. The Messenger of Allah (ﷺ) commanded him to emancipate a slave, or fast for two months, or feed sixty poor men. He said: I cannot provide. The Messenger of Allah (ﷺ) said: Sit down. Thereafter a huge basket of dates (‘araq) was brought to the Messenger of Allah (ﷺ). He said: Take this and give it as sadaqah (alms). He said: Messenger of Allah, there is no poorer than I. The Messenger of Allah (ﷺ) thereupon laughed so that his canine
Grade: Sahih

Hadith #2398 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Aisha bint Abi Bakr; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Yahya bin Sa'id al-Ansari يحيى بن سعيد الأنصاري (Sunan Abi Dawud)
A man came to the Prophet (ﷺ) and said: Messenger of Allah, I ate and drank in forgetfulness when I was fasting. Hie said: Allah had fed you and given you drink.
Grade: Sahih

Hadith #2426 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Abdur-Razzaq عبد الرزاق بن همام; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ma'mar bin Rashid معمر بن راشد; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي (Sunan Abi Dawud)
He said: Messenger of Allah, tell me about keeping fast on Monday and Thursday. He said: On it I was born, and on it the Qur’an was first revealed to me.
Grade: Sahih

Hadith #2433 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Salm Abi al-Nadr سالم بن أبي أمية - أبو النضر (Sunan Abi Dawud)
The Prophet (ﷺ) as saying: If anyone fasts during Ramadan, then follows it with six days in Shawwal, it will be like a perpetual fast.
Grade: Sahih

Hadith #2434 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) used to fast to such an extent that we thought that he would never break his fast, and he would go without fasting to such an extent that we thought he would never fast. I never saw the Messenger of Allah (ﷺ) fast a complete month except in Ramadan, and I never saw his fast more in any month than in Sha’ban.
Grade: Sahih

Hadith #2508 - Sunan Abi Dawud - Abdul Warith bin Sa'id bin Dhakwan عبد الوارث بن سعيد بن ذكوان; Abdullah bin 'Amr, Abu Ma'mar al-Mad'aq عبد الله بن عمرو - أبو معمر المقعد; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Husain bin Dhakwan al-Mua'lam الحسين بن ذكوان المعلم المكتب; Basr bin Sa'id al-Madni بسر بن سعيد المدني العابد; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي; Zayd bin Khalid al-Juhni (Sunan Abi Dawud)
Anas bin Malik reported on the authority of his father, The Apostle of Allaah(ﷺ) said “ You left behind some people in Madeenah who did not fail to be with you wherever you went and whatever you spent (of your goods) and whatever valley you crossed. They asked Apostle of Allaah(ﷺ) how can they be with us when they are still in Madeenah? He replied “They were declined by a valid excuse.”
Grade: Sahih

Hadith #2536 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي (Sunan Abi Dawud)
The Prophet (ﷺ) said: Our Lord Most High is pleased with a man who fights in the path of Allah, the Exalted; then his companions fled away (i.e. retreated). But he knew that it was a sin (to flee away from the battlefield), so he returned, and his blood was shed. Thereupon Allah, the Exalted, says to His angels: Look at My servant; he returned seeking what I have for him (i.e. the reward), and fearing (the punishment) I have, until his blood was shed.
Grade: Hasan

Hadith #2577 - Sunan Abi Dawud - Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Hisham bin 'Urwa هشام بن عروة; Ibrahim bin Muhammad bin al-Harith إبراهيم بن محمد أبو اسحاق الفزاري; Urwa ibn al-Zubayr عروة بن الزبير (Sunan Abi Dawud)
The Prophet (ﷺ) used to hold a race between horses and kept the one in the fifth year at a long distance.
Grade: Sahih

Hadith #2607 - Sunan Abi Dawud - Abu Sa'id al-Khudri; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ali bin Bhr bin Bry علي بن بحر بن بري; Hatm bin Isma'il al-Madni حاتم بن إسماعيل المدني; Muhammad bin Ajlan al-Madni محمد بن عجلان المدني; Nafie' نافع مولى ابن عمر (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) said: A single rider is a devil, and a pair of riders are a pair of devils, but three are a company of riders.
Grade: Hasan

Hadith #2608 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ali bin Bhr bin Bry علي بن بحر بن بري; Hatm bin Isma'il al-Madni حاتم بن إسماعيل المدني; Muhammad bin Ajlan al-Madni محمد بن عجلان المدني; Nafie' نافع مولى ابن عمر (Sunan Abi Dawud)
The Prophet (ﷺ) said: When three are on a journey, they should appoint one of them as their commander.
Grade: Hasan Sahih

Hadith #2843 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ma'mar bin Rashid معمر بن راشد (Sunan Abi Dawud)
When a boy was born to one of us in the pre-Islamic period, we sacrificed a sheep and smeared his head with its blood; but when Allah brought Islam, we sacrificed a sheep, shaved his head and smeared his head with saffron.
Grade: Hasan Sahih

Hadith #2955 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ahmad bin Hanbal أحمد بن حنبل; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Jabir ibn 'Abdullah; Ma'mar bin Rashid معمر بن راشد (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: If anyone leaves property, it goes to his heirs. And if anyone leaves dependents (without resources), they come to us.
Grade: Sahih

Hadith #3084 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Prophet (ﷺ) protected Naqi and said: There is no (permission for) protected land except for Allah Most High.
Grade: Sahih

Hadith #3113 - Sunan Abi Dawud - Abu Sa'id al-Khudri; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Muhammad bin Ibrahim bin al-Harith محمد بن إبراهيم بن الحارث; Sa'id bin Abi Maryam سعيد بن أبي مريم; Yahya bin Ayoub al-Ghafiqi يحيى بن أيوب الغافقي; Yazid bin 'Abdullah bin Usama B. al-Haad يزيد بن عبد الله بن أسامة بن الهاد (Sunan Abi Dawud)
I heard the Messenger of Allah (ﷺ) say three days before his death: No one of you dies but he had good faith in Allah.
Grade: Sahih

Hadith #3119 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ahmad bin Hanbal أحمد بن حنبل; Aisha bint Abi Bakr; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ma'mar bin Rashid معمر بن راشد (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: When one of you is afflicted with a calamity, he should say: “We belong to Allah, and to Him we do return.” O Allah, I expect reward from Thee from this affliction, so give me reward for it, and give me a better compensation.
Grade: Sahih

Hadith #3176 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ma'mar bin Rashid معمر بن راشد; Thawban bin Bujdud; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي; Yahya bin Musa Khat يحيى بن موسى خت (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) used to stand up for a funeral until the corpse was placed in the grave. A learned Jew (once) passed him and said: This is how we do. The Prophet (ﷺ) sat down and said: Sit down and act differently from them.
Grade: Hasan

Hadith #3189 - Sunan Abi Dawud - Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Aisha bint Abi Bakr; al-Dahhak bin 'Uthman bin 'Abdullah الضحاك بن عثمان بن عبد الله بن خالد; Harun bin 'Abdullah al-Hamal هارون بن عبد الله بن مروان الحمال; Muhammad bin Abi Fadayk محمد بن إسماعيل بن مسلم بن أبي فديك; Salm Abi al-Nadr سالم بن أبي أمية - أبو النضر (Sunan Abi Dawud)
I swear by Allah, the Messenger of Allah (ﷺ) prayed over Suhail b. al-Baida’ in the mosque.
Grade: Sahih

Hadith #3198 - Sunan Abi Dawud - Abdul 'Aziz bin Yahya bin Yusuf عبد العزيز بن يحيى بن يوسف البكائي; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ibn Ishaq محمد بن إسحاق بن يسار‎; Muhammad bin Ibrahim bin al-Harith محمد بن إبراهيم بن الحارث; Muhammad bin Salmah محمد بن سلمة بن عبد الله الباهلي (Sunan Abi Dawud)
I prayed over a dead person along with Ibn ‘Abbas. He recited Surat al-Fatihah and he said: This is the Sunnah.
Grade: Sahih

Hadith #3200 - Sunan Abi Dawud - Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Musa bin Mrwan موسى بن مروان; Shu'aib bin Ishaq bin 'Abdur Rahman شعيب بن إسحاق بن عبد الرحمن; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan Abi Dawud)
I was present with Marwan who asked AbuHurayrah: Did you hear how the Messenger of Allah (ﷺ) used to pray over the dead? He said: Even with the words that you said. (The narrator said: They exchanged hot words between them before that.) Abu Hurairah said: O Allah, Thou art its Lord. Thou didst create it, Thou didst guide it to Islam, Thou hast taken its spirit, and Thou knowest best its inner nature and outer aspect. We have come as intercessors, so forgive him. Abu Dawud said: Shu’bah made
Grade: Hasan

Hadith #3282 - Sunan Abi Dawud - Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي (Sunan Abi Dawud)
I said: Messenger of Allah, I have a slave girl whom I slapped. This grieved the Messenger of Allah (ﷺ). I said to him: Should I not emancipate her? He said: Bring her to me. He said: Then I brought her. He asked: Where is Allah ? She replied: In the heaven. He said: Who am I ? She replied: You are the Messenger of Allah. He said: Emancipate her, she is a believer.
Grade: Sahih

Hadith #3289 - Sunan Abi Dawud - Abdullah bin Mubarak عبد الله بن المبارك; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Aisha bint Abi Bakr; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: If anyone vows to obey Allah, let him obey Him, but if anyone vows to disobey Him, let him not disobey Him.
Grade: Sahih

Hadith #3342 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Jabir ibn 'Abdullah; Ma'mar bin Rashid معمر بن راشد; Muhammad bin Abi Sari محمد بن أبي السري (Sunan Abi Dawud)
The Prophet (ﷺ) said: After the grave sins which Allah has prohibited the greatest sin is that a man dies while he has debt due from him and does not leave anything to pay it off, and meets Him with it.
Grade: Da'if

Hadith #3460 - Sunan Abi Dawud - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة (Sunan Abi Dawud)
The Prophet (ﷺ) said: If anyone rescinds a sale with a Muslim, Allah will cancel his slip, on the Day of Resurrection.
Grade: Sahih

Hadith #3513 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ahmad bin Hanbal أحمد بن حنبل; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Jabir ibn 'Abdullah; Ma'mar bin Rashid معمر بن راشد (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: There is the right of option regarding everything which is shared, whether a dwelling or a garden. It is not lawful to sell before informing one’s partner, but if he sells without informing him, he has the greatest right to it.
Grade: Sahih

Hadith #3549 - Sunan Abi Dawud - Aban bin Tghlb أبان بن تغلب; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Jabir ibn 'Abdullah; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
A similar tradition has also been transmitted by Samurah from the Prophet (ﷺ) through a different chain of narrators.
Grade: Sahih

Hadith #3551 - Sunan Abi Dawud - Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ahmed bin Abi al-Hawari أحمد بن عبد الله بن ميمون; al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Jabir ibn 'Abdullah; Urwa ibn al-Zubayr عروة بن الزبير (Sunan Abi Dawud)
The Prophet (ﷺ) said: If anyone is given life-tenancy, it belongs to him and to his descendants. His descendants who inherit him will inherit from it.
Grade: Sahih

Hadith #3552 - Sunan Abi Dawud - Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Jabir ibn 'Abdullah; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان (Sunan Abi Dawud)
A similar tradition has also been transmitted by al-Laith b. Sa’d from al-Zuhri, from Abu Salamah from Jabir.
Grade: Sahih

Hadith #3554 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ahmad bin Hanbal أحمد بن حنبل; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Jabir ibn 'Abdullah; Ma'mar bin Rashid معمر بن راشد (Sunan Abi Dawud)
A similar tradition has been transmitted by ‘Aqil from Ibn Shihab and by Yazid b. Abi Habib from Shihab. Al-Auza’i’s wordings vary from those of Ibn Shihab. Fulaih b. Sulaiman also narrated the tradition like that of Malik.
Grade: Sahih

Hadith #3579 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Muhammad bin 'Abdur Rahman b. Abi Dh'ab محمد بن عبد الرحمن بن أبي ذئب (Sunan Abi Dawud)
“We will never employ or we shall not employ (the narrator is doubtful) in our work one who wants it.”
Grade: Sahih

Hadith #3648 - Sunan Abi Dawud - Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan Abi Dawud)
When Mecca was conquered, the Holy Prophet (peace be upon him) stood up. He (Abu Hurairah) then mentioned the sermon of the Holy Prophet (ﷺ). He said: A man of the Yemen, who was called Abu Shah, got up and said: Messenger of Allah! Write it for me. He said: Write it for Abu Shah.
Grade: Sahih

Hadith #3661 - Sunan Abi Dawud - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ali bin Ms'hr علي بن مسهر; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة (Sunan Abi Dawud)
I swear on Allah, it will be better for you that Allah should give guidance to one man through your agency than that you should acquire the red ones among the camels.
Grade: Sahih

Hadith #3681 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Aisha bint Abi Bakr; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Imam Maalik مالك بن أنس بن مالك بن أبي عامر (Sunan Abi Dawud)
The Prophet (ﷺ) said: If a large amount of anything causes intoxication, a small amount of it is prohibited.
Grade: Hasan Sahih

Hadith #3703 - Sunan Abi Dawud - Aban bin Tghlb أبان بن تغلب; Abdullah bin Abi Qatada Ibn Rab'i عبد الله بن أبي قتادة الأنصاري السلمي; Abu Qatada ibn Rab'i; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
The Messenger of Allah(ﷺ) forbade mixing of raisins and dried dates: and unripe dates and fresh dates.
Grade: Sahih

Hadith #3856 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) came to visit me, accompanied by Ali who was convalescing. We had some ripe dates hung up. The Messenger of Allah (ﷺ) got up and began to eat from them. Ali also got up to eat, but the Messenger of Allah (ﷺ) said repeatedly to Ali: Stop, Ali, for you are convalescing, and Ali stopped. She said: I then prepared some barley and beer-root and brought it. The Messenger of Allah (ﷺ) then said: Take some of this, Ali, for it will be more beneficial for you. AbuDawud
Grade: Hasan

Hadith #3910 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Hassan ibn Ali bin Abi Talib; Ma'mar bin Rashid معمر بن راشد; Muhammad bin Abi Sari محمد بن أبي السري (Sunan Abi Dawud)
The Prophet (ﷺ) said: Taking omens is polytheism; taking omens is polytheism. He said it three times. Every one of us has some, but Allah removes it by trust (in Him).
Grade: Sahih

Hadith #4202 - Sunan Abi Dawud - Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Sulayman ibn Yasar سليمان بن يسار مولى ميمونة بنت الحارث (Sunan Abi Dawud)
Do not pluck out grey hair. If any believer grows a grey hair in Islam, he will have light on the Day of Resurrection. (This is Sufyan’s version). Yahya’s version says: Allah will record on his behalf a good deed for it, and will blot out a sin for it.
Grade: Hasan Sahih

Hadith #4323 - Sunan Abi Dawud - Abu Ja'far al-Nafaili عبد الله بن محمد أبو جعفر النفيلي الحران; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Fatima bint Qays; Muhammad bin 'Abdur Rahman b. Abi Dh'ab محمد بن عبد الرحمن بن أبي ذئب; Uthman bin 'Abdur Rahman عثمان بن عبد الرحمن بن مسلم - الطرائفي (Sunan Abi Dawud)
If anyone memorizes ten verses from the beginning of surat al-Kahf, he will be protected from the trial of Dajjal (Antichrist). Abu Dawud said: In this way Hashim al-dastawa’I transmitted it from Qatadah, but he said : “If anyone memorizes the closing verses of surat al-Kahf.” Shu’bah narrated from Qatadah the words “from the end of al-Kahf.
Grade: Sahih

Hadith #4326 - Sunan Abi Dawud - Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Walid bin 'Abdullah bin Jmy' الوليد بن عبد الله بن جميع الزهري; Jabir ibn 'Abdullah; Muhammad bin Fadayl bin Ghazwan محمد بن فضيل بن غزوان (Sunan Abi Dawud)
I heard the crier of the Messenger of Allah (ﷺ) calling : Assemble for the prayer. I Then came out and prayed along with the Messenger of Allah (ﷺ): When the Messenger of Allah (ﷺ) finished his prayer, he sat on the pulpit laughing, and he said : Everyone should remain where he had said his prayer. He then asked : Do you know why I have assembled you? They said: Allah and His Messenger know best. He (ﷺ) said: I did not call you together fors some alarming news or for something good. Rath
Grade: Sahih

Hadith #4332 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Mua'dh bin Mua'dh bin Nsr معاذ بن معاذ بن نصر; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Ubaidullah bin Mua'dh عبيد الله بن معاذ بن معاذ بن نصر (Sunan Abi Dawud)
We saw the last of Ibn Sayyad at the battle of the Harrah.
Grade: Sahih

Hadith #4428 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Hassan ibn Ali bin Abi Talib; Jabir ibn 'Abdullah; Ma'mar bin Rashid معمر بن راشد; Muhammad bin Abi Sari محمد بن أبي السري (Sunan Abi Dawud)
A man of the tribe of Aslam came to the Prophet (ﷺ) and testified four times against himself that he had had illicit intercourse with a woman, while all the time the Prophet (ﷺ) was turning away from him. Then when he confessed a fifth time, he turned round and asked: Did you have intercourse with her? He replied: Yes. He asked: Have you done it so that your sexual organ penetrated hers? He replied: Yes. He asked: Have you done it like a collyrium stick when enclosed in its case and a rope i
Grade: Hasan

Hadith #4475 - Sunan Abi Dawud - Abu Damra, Anas bin 'Ayyad أنس بن عياض الليثي - أبو ضمرة; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Muhammad bin Ibrahim bin al-Harith محمد بن إبراهيم بن الحارث; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Yazid bin 'Abdullah bin Usama B. al-Haad يزيد بن عبد الله بن أسامة بن الهاد (Sunan Abi Dawud)
He (the Prophet) commanded regarding the two men and the woman who spoke obscenity were Hassan ibn Thabit and Mistah ibn Uthathah. An-Nufayl said: It is said that the woman was Hammah daughter of Jahsh.
Grade: Hasan

Hadith #4482 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Muhammad bin 'Abdur Rahman b. Abi Dh'ab محمد بن عبد الرحمن بن أبي ذئب; Nsr bin 'Asim al-Antaky نصر بن عاصم الأنطاكي; Yazid bin Harun يزيد بن هارون (Sunan Abi Dawud)
The Prophet (ﷺ) said: If they (the people) drink wine, flog them, again if they drink it, flog them. Again if they drink it, kill them.
Grade: Hasan Sahih

Hadith #4507 - Sunan Abi Dawud - Aabad bin al-Wam bin عباد بن العوام; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Da'ud bin Rshyd داود بن رشيد; Harun bin 'Abdullah al-Hamal هارون بن عبد الله بن مروان الحمال; Sa'id bin Abi Sa'id; Sa'id bin Sulaiman al-Dabi سعيد بن سليمان - سعدويه الضبي; Sufyan bin Hussain bin al-Hasan سفيان بن حسين السلمي (Sunan Abi Dawud)
The Prophet (ﷺ) said: I will not forgive anyone who kills after accepting blood-wit
Grade: Da'if

Hadith #4509 - Sunan Abi Dawud - Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Wahb bin Bqyh bin 'Uthman وهب بن بقية بن عثمان (Sunan Abi Dawud)
A Jewess presented a poisoned sheep to the Prophet (ﷺ), but the Prophet (ﷺ) did not interfere with he. Abu Dawud said: The Jewess who poisoned the Prophet (ﷺ) was sister of Marhab.
Grade: Da'if

Hadith #4510 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Wahb bin Bqyh bin 'Uthman وهب بن بقية بن عثمان (Sunan Abi Dawud)
Jabir ibn Abdullah used to say that a Jewess from the inhabitants of Khaybar poisoned a roasted sheep and presented it to the Messenger of Allah (ﷺ) who took its foreleg and ate from it. A group of his companions also ate with him. The Messenger of Allah (ﷺ) then said: Take your hands away (from the food). The Messenger of Allah (ﷺ) then sent someone to the Jewess and he called her. He said to her: Have you poisoned this sheep? The Jewess replied: Who has informed you? He said: This forele
Grade: Da'if

Hadith #4524 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ma'mar bin Rashid معمر بن راشد; Sulayman ibn Yasar سليمان بن يسار مولى ميمونة بنت الحارث (Sunan Abi Dawud)
A man of the Ansar was killed at Khaybar and his relatives went to the Prophet (ﷺ) and mentioned that to him. He asked: Have you two witnesses who can testify to the murderer of your friend? They replied: Messenger of Allah! there was not a single Muslim present, but only Jews who sometimes have the audacity to do even greater crimes than this. He said: Then choose fifty of them and demand that they take an oath; but they refused and the Prophet (ﷺ) paid the blood-wit himself.
Grade: Sahih

Hadith #4574 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ahmed bin 'Amr bin al-Sarh أحمد بن عمرو بن السرح أبو الطاهر; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Wahb bin Bayan وهب بن بيان; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد (Sunan Abi Dawud)
About the story of Haml ibn Malik, Ibn Abbas said: She aborted a child who had grown hair and was dead, and the woman also died. He (the Prophet) gave judgment that the blood-wit was to be paid by the woman’s relatives on the father’s side. Her uncle said: Messenger of Allah! She has aborted a child who had grown hair. The father of the woman who had slain said: He is a liar: I swear by Allah, he did not raise his voice, or drink or eat. No compensation is to be paid for an offence like this
Grade: Da'if

Hadith #4577 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ibrahim bin Musa al-Razi al-Fara' إبراهيم بن موسى الرازي الفراء; Isa bin Yonus bin Abi Ishaq عيسى بن يونس بن أبي إسحاق; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة (Sunan Abi Dawud)
About this story: Then the woman, against whom he decided that a male or female should be paid for her, died. The Messenger of Allah (ﷺ) then gave judgement that her sons will inherit from her, and the bloodwit should be paid by her relatives on the father’s side.
Grade: Sahih

Hadith #4591 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Prophet (ﷺ) said: If anyone is killed blindly or, when people are throwing stones, by a stone or a whip, his blood-wit is the blood-wit for an accidental murder. But if anyone is killed intentionally, retaliation is due. If anyone tries to prevent it, the curse of Allah, of angels, and of all the people will rest on him.
Grade: Sahih

Hadith #4594 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Wahb bin Bqyh bin 'Uthman وهب بن بقية بن عثمان (Sunan Abi Dawud)
The Prophet (ﷺ) said: No recompense may be demanded if the fire spreads.
Grade: Sahih

Hadith #4601 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ahmad bin Hanbal أحمد بن حنبل; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Yazid bin Harun يزيد بن هارون (Sunan Abi Dawud)
I came to my family when my hands had cracks. They dyed me with saffron. I then went to Prophet (ﷺ) and saluted him, but he did not return me salutation. He said: Go and wash it away from you.
Grade: Hasan

Hadith #4669 - Sunan Abi Dawud - Abdur Rahman bin Harmaz al-A'araj عبد الرحمن بن هرمز الأعرج أبو داود; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ibrahim bin Sa'd bin Ibrahim إبراهيم بن سعد بن إبراهيم; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان; Ya'qub bin Ibrahim bin Sa'd يعقوب بن إبراهيم بن سعد بن إبراهيم (Sunan Abi Dawud)
It is not fitting for a servent to say that I (The Prophet) is better than Jonah son of Matta.
Grade: Sahih

Hadith #4673 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ahmed bin Salah al-Masri أحمد بن صالح المصري; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد (Sunan Abi Dawud)
I shall be pre-eminent among the descendants of Adam, the first from whom the earth will be cleft open the first intercessor, and the first whose intercession will be accepted.
Grade: Sahih

Hadith #4680 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ahmad bin Hanbal أحمد بن حنبل; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
when the Prophet (May peace be upon him) turned towards the Ka’bah (in prayer), the people asked : Messenger of Allah (May peace be upon him)! what will happen with those who died while they prayed with their faces towards Jerusalem ? Allah the Exalted, then revealed : “And never would Allah make your faith of no effect.”
Grade: Sahih

Hadith #4720 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ibn Ishaq محمد بن إسحاق بن يسار‎; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Salmah bin al-Fadl al-Abrash سلمة بن الفضل الأبرش; Utba bin Muslim al-Madni عتبة بن مسلم المدني (Sunan Abi Dawud)
Do not sit with those who believe in free will and do not address them before they address you.
Grade: Da'if

Hadith #4731 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Salman al-Aghar Abu 'Abdullah سلمان الأغر أبو عبد الله (Sunan Abi Dawud)
I asked: Messenger of Allah! will each one of us see his Lord? Ibn Mu’adh’s version has: “being alone with Him, on the Day of Resurrection? And what sign is there is His creation?” He replied: AbuRazin! does each one of you not see the moon? Ibn Mu’adh’s version has: “on the night when it is full, being alone with it?” Then the agreed version goes: I said: Yes. He said: Allah is more great. Ibn Mu’adh’s version has: It is only part of Allah’s creation, but Allah is more gl
Grade: Hasan

Hadith #4742 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي (Sunan Abi Dawud)
The Prophet (ﷺ) said: The trumpet (sur) which will be blown.
Grade: Sahih

Hadith #4788 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Bashr bin Rafa'i al-Harithy بشر بن رافع الحارثي; Hjaj bin Frafs'h حجاج بن فرافصة الباهلي; Muhammad bin 'Abdullah bin al-Zubair محمد بن عبد الله أبو أحمد الزبيري; Muhammad bin Abi Sari محمد بن أبي السري; Nasr bin 'Ali bin Nasr bin 'Ali; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan Abi Dawud)
When the Prophet (ﷺ) was informed of anything of a certain man, he would not say: What is the matter with so and so that he says? But he would say: What is the matter with the people that they say such and such?
Grade: Sahih

Hadith #4790 - Sunan Abi Dawud - Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Aisha bint Abi Bakr; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي (Sunan Abi Dawud)
The Prophet (ﷺ) said: The believer is simple and generous, but the profligate is deceitful and ignoble.
Grade: Hasan

Hadith #4838 - Sunan Abi Dawud - Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Rabi' bin Nafi' Abu Tawba al-Halbi الربيع بن نافع أبو توبة الحلبي; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Qurrah bin Khalid al-Sadusi قرة بن خالد السدوسي (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) spoke in a distinct and leisurely manner.
Grade: Sahih

Hadith #4930 - Sunan Abi Dawud - Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Aisha bint Abi Bakr; Amarah bin Ghazya bin al-Harith عمارة بن غزية بن الحارث; Muhammad bin Awf bin Sufyan محمد بن عوف بن سفيان الطائي; Muhammad bin Ibrahim bin al-Harith محمد بن إبراهيم بن الحارث; Sa'id bin Abi Maryam سعيد بن أبي مريم; Yahya bin Ayoub al-Ghafiqi يحيى بن أيوب الغافقي (Sunan Abi Dawud)
The Prophet (May peace be upon him) cursed effeminate men (mukhannathan) and women who imitated men, saying: Put them out of your houses, and put so-and-so out. (that is to say, the effeminate men)
Grade: Sahih

Hadith #4938 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) said: He who plays backgammon disobeys Allah and His Apostle.
Grade: Hasan

Hadith #4982 - Sunan Abi Dawud - Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; ibn Umar; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Uthman bin Muhammad (Sunan Abi Dawud)
I was riding on a mount behind the prophet (May peace be upon him). It stumbled. Thereupon I said: May the devil perish! He said: do not say; may the devil perish! For you say that, he will swell so much so that he will be like a house, and say: by my power. But say: in the name of Allah; for when you say that, he will diminish so much so that he will be like a fly.
Grade: Sahih

Hadith #5019 - Sunan Abi Dawud - Abu Ja'far al-Nafaili عبد الله بن محمد أبو جعفر النفيلي الحران; Abu Qatada ibn Rab'i; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Yahya bin Sa'id al-Ansari يحيى بن سعيد الأنصاري; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan Abi Dawud)
When the time draws near, a believer’s vision can hardly be false. The truer one of them is in his speech, the truer he is in his vision. Visions are of three types: Good visions are glad tidings from Allah, a terrifying vision caused by the devil, and the ideas which come from within a man. So when one sees anything he dislikes, he should get up and pray, and should not tell it to the people. He said : I like a fetter and dislike a shackle on the neck; a fetter indicates being firmly establis
Grade: Sahih

Hadith #5021 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ahmed bin Salah al-Masri أحمد بن صالح المصري; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد (Sunan Abi Dawud)
I heard the Messenger of Allah (May peace be upon him) say: A good vision comes from Allah and a dream (hulm) from the devil, so when one of you sees what he dislikes, he must spit on his left (three times), and seek refuge in Allah from its evil. It will then not harm him.
Grade: Sahih

Hadith #5038 - Sunan Abi Dawud - Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan Abi Dawud)
The Jews used to try to sneezes in the presence of the Prophet (ﷺ) hoping that he would say to them: “Allah have mercy on you!” but he would say: May Allah guide you and grant you well-being!
Grade: Sahih

Hadith #5126 - Sunan Abi Dawud - Abdul Malik bin 'Umayr al-Qabti عبد الملك بن عمير بن سويد القبطي; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Shayban bin 'Abdur Rahman شيبان بن عبد الرحمن النحوي أبو معاوية; Yahya bin Abi Bkyr يحيى بن أبي بكير واسمه نسر (Sunan Abi Dawud)
Messenger of Allah! A man loves some people, but he cannot do work like their work. He replied; Yes, Abu Dharr, will be with those whom you love. Abu Dharr then repeated it. The Messenger of Allah (May peace be upon him) also repeated it.
Grade: Sahih

Hadith #5152 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ma'mar bin Rashid معمر بن راشد; Muhammad bin Abi Sari محمد بن أبي السري (Sunan Abi Dawud)
Mujahid said that Abdullah ibn Amr slaughtered a sheep and said: Have you presented a gift from it to my neighbour, the Jew, for I heard the Messenger of Allah (ﷺ) say: Gabriel kept on commending the neighbour to me so that I thought he would make an heir?
Grade: Sahih

Hadith #5186 - Sunan Abi Dawud - Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Isma'il bin Ja'far bin Abi Kathir إسماعيل بن جعفر بن أبي كثير الأنصاري; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Naf' bin Abd al-Harith; Yahya bin Ayoub al-Maqabri يحيى بن أيوب المقابري (Sunan Abi Dawud)
When the Messenger of Allah (ﷺ) came to some people’s door, he did not face it squarely, but faced the right or left corner, and said: Peace be upon you! peace be upon you! That was because there were no curtains on the doors of the house at that time.
Grade: Sahih

Hadith #5216 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
when he came near the mosque, he said to the Ansar; stand up showing respect to your chief.
Grade: Sahih

Hadith #5230 - Sunan Abi Dawud - Abdul Rahim bin Sulaiman عبد الرحيم بن سليمان الكناني; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Aisha bint Abi Bakr; Amir al-Sha'bi عامر الشعبي; Zakaria bin Abi Za'idah زكريا بن أبي زائدة خالد (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) came out to us leaning on a stick. We stood up to show respect to him. He said: Do not stand up as foreigners do for showing respect to one another.
Grade: Da'if

Hadith #5264 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ahmed bin Salah al-Masri أحمد بن صالح المصري; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد (Sunan Abi Dawud)
The Prophet (ﷺ) said: For the first blow seventy good deeds will be recorded.
Grade: Sahih